Implementasi Algoritma Naive Bayes Untuk Mengetahui Minat Beli Konsumen Terhadap Sarang Burung Walet - Sofyan Sofyan; Siti Nur Asia; Mardewi Mardewi (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2021)
Implementation of the Naive Bayes Algorithm to determine consumer buying interest in swallow nests. This study implements the Naive Bayes algorithm for managing data analysis which is used to classify new case data based on samples from training data by calculating the probability or probability value of each class. The number of samples used in this analysis is 25 training data records that are calculated manually or using the rapidminer application. The results of the calculation by applying the nave Bayes algorithm by multiplying the probability value or the probability value of the cases taken from the training data can be seen that P(X|Classification=”Interest”) gets greater results than P(X|Classification='No” ) with a value of interest = 0.233739 and a value of 0.00078. In addition, the results of data processing with the rapidminer application show that the new case data in the training data is included in the